Gap‐Plasmon Induced One‐Order Enhancement of Optical Anisotropy of 2D Black Phosphorus. Issue 1 (13th September 2020) - Jia, Jingyuan; Chen, Xiaoming; Ban, Yu; Zhang, Xinyue; Liu, Kuan; Guo, Yaoming; Chui, Hsiang-Chen; Long, Yi; Cao, Tun
Abstract : Anisotropic 2D materials with unique thermoelectric, electrical, and optical characteristics offer prospects for various angle‐dependent devices. Yet, few anisotropic 2D materials are exploited. Black phosphorus (BP) is a newly rediscovered 2D material with striking in‐plane anisotropy. However, experimental illustrations of the optical anisotropy of 2D BP are very limited presumably due to the ultrathin thickness of the few‐layered BP which weakens the light–matter interaction. To solve this problem, herein a hybrid nanostructure is fabricated using a one‐step self‐assembly deposition of gold (Au) nanoparticle (NP) clusters onto the few‐layered BP residing on a silica (SiO2 ) substrate. Such a hybrid nanostructure can squeeze the light into AuNPs–SiO2 gap through the gap plasmon resonance, enabling the confined light to interact efficiently with the ultrathin BP film. Angle‐resolved polarized Raman spectra measurement is carried out to study the influence of the AuNPs on the in‐plane optical anisotropy of the BP. About 20 times enhancement of Raman intensity anisotropy is experimentally achieved using AuNPs. The AuNPs‐BP system is not only useful for high‐performance polarization‐dependent photonic devices but also a universal methodology for exploring the in‐plane anisotropy of low‐symmetry 2D materials. Furthermore, the high‐throughput self‐assembly fabrication shows its potential for industrial‐scale manufacturability. Abstract : An approach is developed to significantly enhance the optical anisotropy of the four‐layered BP flake. The enhancement is achieved by dispersing AuNPs onto the BP flake without any complex nanofabrication. Moreover, the polarization‐dependent Raman peak intensities from the structures not only confirm the optical anisotropy enhancement factor of 20 but clearly identify the crystal orientations of four‐layered BP.